Influence of supplemental protein concentration on the performance of beef cows grazing dormant bluestem range - T. DelCurto; B. Cochran; L. Corah (Kansas Agricultural Experiment Station Research Reports, 1988)
Three milo/soybean meal mixtures representing three supplemental crude protein concentrations (13, 26, and 39%) were evaluated in terms of pregnant beef cow performance. Cow weight and body condition changes responded in a linear fashion to increasing protein. Cattle fed the high protein (39% Crude Protein) supplement lost the least weight and body condition, whereas cattle supplemented with the low protein treatment lost the most. Although there was little difference between treatment groups in terms of reproductive efficiency and subsequent calf performance, moderate (26% Crude Protein) and high protein supplements appear to offer the most benefit in maintaining cow\weight and body condition during the critical winter months up to calving.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Protein; Beef Cows; Performance; Dormant bluestem